Chinese Olympic sport policy: Managing the impact of globalisation - Tan, T.-C.; Houlihan, B. (International Review for the Sociology of Sport, 2013)
The article examines the extent to which, and the manner in which, the Chinese government managed its relationship with the Olympic movement following its re-engagement with international elite sport competition in the mid 1970s. Locating the analysis in the literature on globalisation, the article notes the limited research exploring the role of the state in managing the relationship between domestic and global sport. Based on extensive document analysis and interviews, the article provides an analysis of the governmental strategy to increase Chinese influence in the Olympic movement, produce a strong national Olympic squad of athletes and ensure success at the 2008 Beijing Olympic Games. It is argued that the Chinese state was not only effective in organising and concentrating resources to support its policy objectives, but was also able to incorporate aspects of market capitalism into its elite development system and, so far at least, generally manage effectively the tensions that arose from an increasingly wealthy, mobile and individualistic cohort of elite athletes and coaches.